Desenvolvimento de um sistema microcontrolado para aplicação de potenciais variáveis tipo potenciostato - Siepmann, David Antonio Brum (2019)
Analysis of electrochemical solutions can be performed by applying a voltage signal as excitation and evaluating the resulting current in the sample, the device performing this function is called potentiostat. The high cost to acquire such a device makes it difficult to research and teach in the field of electrochemistry in many laboratories for analysis in environmental and agricultural applications. Thus, a low-cost microcontrolled device was developed along with a graphical user interface, allowing accurate voltammetric studies. The evaluation behavior of the device in tests that demonstrate low level of distortion for the applied signal and low noise in the current measurement in the scales of 20 and 2 mA, with a cost of R$ 180.00 for components acquisition. Thus, the results in the characterization provide accurate and coherent readings with the literature, being possible to measure the diffusion coefficient in copper salts. Allowing the use of the device in research and teaching can be replicated at a low-cost.